CONCEPTUAL MODEL DESIGN OF SUSTAINABLE PALM SHELL SUPPLY CHAIN BUSINESS PROCESSES - Defi Norita (Journal of Industrial Engineering Management, 2022)
This study aimed to design a graphical conceptual model of the sustainable palm kernel shell processing industry in Indonesia. This study used system entity analysis and Business Process Modeling Notation (BPMN 2.0) to find out the conceptual model of sustainable palm kernel shell industrial processing including procurement of palm kernel shell to be processed into several high value-added products such as coal briquette fuel, feed mixtures livestock, and road paving materials. The conceptual model in the form of a system entity model and business process was integrated with sustainable economic, social, and environmental concepts. The conceptual model can be the basis for the development of other models at the strategic, planning, and operational levels of the sustainable palm kernel shell supply chain.